Cloning and functional analysis of BMP3 in the pearl oyster (Pinctada fucata). Issue 1 (1st January 2019) - Fan, Sigang; Zhou, Daizhi; Xu, Youhou; Yu, Dahui
ABSTRACT: Bone morphogenetic proteins (BMPs) are multifunctional secreted cytokines that play important roles in bone formation. In the present study, a homologous BMP3 gene was identified from Pinctada fucata ( PfBMP3 ). PfBMP3 was 2710 bp length, contained 1470 bp of ORFs. PfBMP3 gene was expressed at all stages tested, with the highest expression during the trochophore and metamorphosis stages. PfBMP3 gene was expressed in all tissues tested, with high levels detected in the gill and mantle. In situ hybridization of the mantle revealed that PfBMP3 was highly expressed in the inner epidermis of the inner fold, the outer epidermis of the middle fold, and outer epidermis of the mantle. In the shell notching experiments, the expression of PfBMP3 was up-regulated after treatment. These results indicated that PfBMP3 might play a role in P. fucata shell formation . The expression level of PfBMP3 in a low calcium aquacultural environment was higher than that in a high calcium aquacultural environment, suggesting that PfBMP3 might participate in calcium ion metabolism regulation. RNA interference (RNAi) showed that the expression level of the calmodulin gene PfCaM was down-regulated after RNAi, implying that the involvement of PfBMP3 in calcium ion metabolism might be through action with PfCaM .